Lexical Variation of Sasak Kuto-Kute Dialect in North Lombok District - Sarwadi, Gita; Mahsun, Mahsun; Burhanuddin, Burhanuddin (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Despite Sasak community in five sub-districts of North Lombok uses the same dialect, namely kuto-Kute Dialect (BSDK), the people within those sub-districts demonstrate different lexicals to express the same meaning. The purpose of this study is to describe the lexicals variations in Kuto-Kute Dialect used by the community in North Lombok. This study used a descriptive-qualitative method. The data was taken by using observation and conversational method. Observation method was applied by observing the language used by communities within the observation spots in the village, while conversational method was used by having conversations with the informants from the observed villages. The data was analysed by using referential identity and distributional methods. The result of the analysis showed that Sasak Kuto-Kute dialect in certain gloss has lexical variations they are glosses having two lexical variation and three lexical variations.